(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2021)
This study focuses on distribution pattern, diversity and phytosociology of tree species associated with traditional agroforestry in Poonch district of Jammu and Kashmir, India. Data was collected from fifty quadrats (10×10m) sized thrown randomly in agriculture fields. Twenty six tree species belonging to 16 families and 21 genera were encountered. Grewia optiva, Pyrus persica and Celtis australis were the dominant tree species. Grewia optiva was the most dense tree species 3.88 stem/ha followed by Pyrus persica with 3.74 stem/ha. Buxus wallichiana was recorded as the least dense species (0.82 stem/ha). The study revealed that the area has vast potential sites for the plantation of various agroforestry tree species to solve fuel, fodder and timber. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 77-82